Probing the angular and polarization reconstruction of the ARIANNA detector at the South Pole - Anker, A.; Barwick, S. W.; Klein, S. R.; Kleinfelder, S. A.; Lahmann, R.; Latif, U.; Meyers, Z. S.; Nam, J.; Novikov, A.; Nelles, A.; Paul, M. P.; Persichilli, C.; et al. (Journal of Instrumentation, 2020)
The sources of ultra-high energy (UHE) cosmic rays, which can have energies up to 10$^{20}$ eV, remain a mystery. UHE neutrinos may provide important clues to understanding the nature of cosmic-ray sources. ARIANNA aims to detect UHE neutrinos via radio (Askaryan) emission from particle showers when a neutrino interacts with ice, which is an efficient method for neutrinos with energies between 10$^{16}$ eV and 10$^{20}$ eV. The ARIANNA radio detectors are located in Antarctic ice just beneath the surface. Neutrino observation requires that radio pulses propagate to the antennas at the surface with minimum distortion by the ice and firn medium. Using the residual hole from the South Pole Ice Core Project, radio pulses were emitted from a transmitter located up to 1.7 km below the snow surface. By measuring these signals with an ARIANNA surface station, the angular and polarization reconstruction abilities are quantified, which are required to measure the direction of the neutrino. After deconvolving the raw signals for the detector response and attenuation from propagation through the ice, the signal pulses show no significant distortion and agree with a reference measurement of the emitter made in an anechoic chamber. Furthermore, the signal pulses reveal no significant birefringence for our tested geometry of mostly vertical ice propagation. The origin of the transmitted radio pulse was measured with an angular resolution of 0.37ˆ indicating that the neutrino direction can be determined with good precision if the polarization of the radio-pulse can be well determined. In the present study we obtained a resolution of the polarization vector of 2.7ˆ. Neither measurement show a significant offset relative to expectation.